Article Review: Mutation Breeding of Soybean (Glycine max L.) Anjasmoro Variety Using Gamma Radiation Co-60 - Beliya, Tesa; Violita (Microbiotech, 2024)
This study examines the utilization of gamma radiation, particularly from the Co-60 source, for mutation breeding in soybean plants (Glycine max L.), with a focus on the Anjasmoro variety. Gamma radiation has the capability to induce genetic mutations that can enhance genetic diversity and desirable traits in plants. The determination of optimal radiation doses, indicated by Lethal Dose (LD) values, is a critical factor in the success of mutation breeding. LD50 and LD20 are often used as parameters to evaluate the effectiveness of induced mutations. The Anjasmoro variety is known for its superior characteristics, such as tolerance to waterlogged conditions, high seed yield, and elevated protein and fat content. The application of gamma radiation to this variety aims to further improve the productivity and quality of soybean crops in Indonesia.